2021
DOI: 10.1097/md.0000000000025334
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment and outcome of upper cervical spine fractures in young children

Abstract: Cervical spine (C-spine) fractures in young children are very rare, and little information on treatment modalities and functional, radiographic, and patient-reported outcome exists. In this 2-center, retrospective case series, we assessed subjective and functional mid-term outcomes in children aged ≤5 years whose C-spine fractures were treated nonoperatively. Between 2000 and 2018, 6 children (median age at injury: 23.5 months; range: 16–31 months) with C1 or C2 injuries were treated with Minerva ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“… 9 In patients with unstable fractures but normal spinal cord alignment, conservative management has been shown to be effective. 9 , 19 In the neonatal population, surgical treatment is challenging, as instrumentation is not suitable and bony fusion with an autograft or allograft also requires immobilization for arthrodesis. Custom orthoses present an attractive alternative to facilitate healing and may be sufficient in this patient population for most injury types.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In patients with unstable fractures but normal spinal cord alignment, conservative management has been shown to be effective. 9 , 19 In the neonatal population, surgical treatment is challenging, as instrumentation is not suitable and bony fusion with an autograft or allograft also requires immobilization for arthrodesis. Custom orthoses present an attractive alternative to facilitate healing and may be sufficient in this patient population for most injury types.…”
Section: Discussionmentioning
confidence: 99%
“…The median time to healing of cervical spine fractures, which are the fractures closest to the type we describe, is 8.5 weeks. 13 In the time course of fracture healing, the initial type of bone deposited at the fracture site is woven bone, which is disorganized. After a time, lamellar bone is formed, which has much more strength.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative approaches play a central role in the treatment and management of pediatric cervical spine injuries. In an 18-year, two-center retrospective study, Tomaszewski et al (n=6) found that nonoperative management using conservative cervical orthosis resulted in satisfactory subjective and functional outcomes with no observed complications [ 20 ]. Conservative management was largely effective for the study population in this review.…”
Section: Discussionmentioning
confidence: 99%